7.3: A Simulation Study of a Flat Panel Detector Based on Shadow Mask PDP. Issue 1 (1st July 2013) - Zhang, Panpan; Tu, Yan; Yang, Lanan; Ma, Shanle; Zhang, Wei; Tolner, Harm
Abstract A new type of detector, the shadow mask flat panel detector, is proposed and its characteristics are investigated by the program Garfield. The results reveal how the avalanche process and gain of the detector depend on the voltages applied and the structure. It proves that higher positive anode voltage and lower negative shadow mask voltage can enhance the gain. To ease the limitation of the Paschen breakdown, a new design enabling high gain values by suppressing ion feedback is proposed.